Characteristics of older cyclists with self-perceived needs for improvement in cycling competence: SiFAr trial - Keppner, Veronika; Sieber, Cornel; Freiberger, Ellen; Kob, Robert; Krumpoch, Sebastian; Siebentritt, Hanna (European Geriatric Medicine, 2023)
Background: Older cyclists are in great risk of being injured or killed in a traffic-related accident and their needs should find more consideration in safety guidelines, urban planning, and future intervention programs. Objective: The aim for this cross-sectional analysis was to comprehensively explore characteristics of community-dwelling cyclists aged 65 years and older with a self-perceived need to increase cycle competence. Methods: 118 older adults (mean age 73.3 ± 5.2 years, 61% women) performed a standardized cycle course representing specific cycling skills. Additionally, health and functional assessments were carried out and characteristics regarding demographic, health, falls, bicycle equipment/type and cycling biography/behavior were obtained. Results: The majority (67.8%) of this community-dwelling adults reported being unsafe when cycling and 41.3% had a bicycle fall in the past year. More than half of the participants showed at least one limitation in each of the measured cycling skills. Women significantly had more frequent limitations in four of the cycling skills measured (p ≤ 0.001) compared to men. While no significant differences were found for falls, health and functional characteristics, women and men differed significantly in terms of bicycle type, equipment, and perceived safety (p < 0.001). Conclusion: Limitations in cycling should be compensated by preventive bicycle training and a safe cycling infrastructure. Bicycle fit, the wearing of bicycle helmets and promotion of a sense of security while cycling can further reduce accident risk and must find recognition in safety guidelines. In addition, educational initiatives have to dismantle gender-related bicycle stereotypes.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Aging; Cycling; Cycling safety; e-bike; Older adults